2022
DOI: 10.1071/mf22023
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater sponges overgrow the invasive golden mussel

Abstract: The golden mussel Limnoperna fortunei is one of the top three invasive animals in Brazil. It is widely distributed in South America, changing the whole environment, and causing exorbitant expenses for hydroelectric power plants (HPPs). The aim of this report is to record freshwater sponges as a natural enemy of the invasive mussel in the Upper Paraná River. Specimens of six native sponge species were observed overgrowing the L. fortunei in SCUBA dives conducted in three HPP reservoirs. This type of competitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In contrast, the presence of the Pereira Barreto Channel mixes water from Ilha Solteira and Três Irmãos reservoirs turning their physico-chemical parameters more similar. All of this affects the abundance and distribution of the golden mussel, which reaches highest densities in a more eutrophic region, especially artificial ones 42 , 78 . The more the dams interfere in the natural limnological conditions more difficult will be to manage the bioinvasive species, since abiotic factors are directly related to species presence and abundance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the presence of the Pereira Barreto Channel mixes water from Ilha Solteira and Três Irmãos reservoirs turning their physico-chemical parameters more similar. All of this affects the abundance and distribution of the golden mussel, which reaches highest densities in a more eutrophic region, especially artificial ones 42 , 78 . The more the dams interfere in the natural limnological conditions more difficult will be to manage the bioinvasive species, since abiotic factors are directly related to species presence and abundance.…”
Section: Resultsmentioning
confidence: 99%
“…This is an invasive mollusk that has been causing extensive environmental impact in the South America inland waters since the years 1990 41 . In the study area, the species intensively competes for space with native benthic species, such as freshwater sponges, 42 with a preference for low-water-velocity regions (<0.1 m/s), and adults reaching levels close to the carrying capacity (1.7 kg/m2), after 540 days, via mathematical and computational modeling 43 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, inter-basin water transfer projects have increased dramatically due to human water management needs, and long-distance water transfers pose a serious risk of biological invasions (Barbosa et al, 2018;Pyšek et al, 2020;Haubrock et al, 2022;Zhang et al, 2022;Mahapatra et al, 2023). These aquatic organisms have spread to many parts of the world, such as North American, South American, and European continents (de Medeiros Fortunato & Andrade Figueira, 2022;Elizarraga et al, 2023). Their attachment corrodes concrete walls, increases flow resistance, clogs pipes and damages the structure of man-made buildings (Boltovskoy et al, 2022;de Souza et al, 2023), which cost $ 63.7 billion (2017 US$) across all regions and socioeconomic sectors between 1980 and 2020 (Haubrock et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Risks of L. fortunei on the human environmentIt is reported that a large number of man-made structures and facilities have serious fouling problems caused by L. fortunei, including water and wastewater processing plants, municipal and industrial water supply systems, water intake structures of drinking water treatment plants, water transfer canals and aqueducts, agricultural irrigation systems, balancing reservoirs and balancing tanks, watercraft, fish culture facilities, steel mills, refineries, aquaculture, ship transit, nuclear power plants, hydroelectric power plants, and thermal power plants(Boltovskoy et al 2015b;Uliano-Silva et al 2017;de Medeiros Fortunato & Andrade Figueira 2022).…”
mentioning
confidence: 99%